Alkyl chain length effects on double-deck assembly at a liquid/solid interface. Issue 31 (27th July 2018) - Fang, Yuan; Cibian, Mihaela; Hanan, Garry S.; Perepichka, Dmitrii F.; De Feyter, Steven; Cuccia, Louis A.; Ivasenko, Oleksandr
Abstract : Controlled double-deck packing is an appealing means to expand upon conventional 2D self-assembly which is critical in crystal engineering, yet it is rare and poorly understood. Abstract : Controlled double-deck packing is an appealing means to expand upon conventional 2D self-assembly which is critical in crystal engineering, yet it is rare and poorly understood. Herein, we report the first systematic study of double-deck assembly in a series of alkylated aminoquinone derivatives at the liquid–solid interface. The competition between the fraction of alkyl chains adsorbed on the surface and the optimal conformation of the alkyl chains near the head group leads to a stepwise structural transformation ranging from complete double-deck packing to complete monolayer packing. Alkyl chains on the bottom or top layer of the double-deck assemblies were selectively visualized by carefully tuning the scanning tunneling microscopy settings. A method to easily identify mirror image domains was discovered based on the coincidence of domain boundaries with a graphite main axis. The effect of molecular symmetry and metal complexation on the formation of the double-deck assembly was also explored. Based on 2D crystal engineering principles, this bottom-up double-deck assembly can potentially provide an essential toehold for constructing precise 3D hierarchical structures.